2005
DOI: 10.1109/tbme.2005.857677
|View full text |Cite
|
Sign up to set email alerts
|

Current Density Imaging and Electrically Induced Skin Burns Under Surface Electrodes

Abstract: Abstract-The origin of electrical burns under gel-type surface electrodes is a controversial topic that is not well understood. To investigate the phenomenon, we have developed an excised porcine skin-gel model, and used low-frequency current density imaging (LFCDI) to determine the current density (CD) distribution through the skin before and after burns were induced by application of electrical current (200 Hz, 70% duty cycle, 20-35 mA monophasic square waveform applied to the electrodes for 30-135 min). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…A previous study based on ultrasonic imaging techniques demonstrated that the skin is thicker on the dorsal than volar forearm [26]. Even within the skin area under a surface gel-type electrode, the electrical current density is distributed unevenly due to uneven skin resistivity [27]. The result that E1 and E2 (ventral side) had lower PTs while E4 (dorsal side) had a higher PT, assists to strengthen our speculation that lower skin impedance led to lower PT.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study based on ultrasonic imaging techniques demonstrated that the skin is thicker on the dorsal than volar forearm [26]. Even within the skin area under a surface gel-type electrode, the electrical current density is distributed unevenly due to uneven skin resistivity [27]. The result that E1 and E2 (ventral side) had lower PTs while E4 (dorsal side) had a higher PT, assists to strengthen our speculation that lower skin impedance led to lower PT.…”
Section: Discussionmentioning
confidence: 99%
“…Surface electrodes are the most commonly used electrodes clinically, in applications as diverse as functional electrical stimulation for the restoration of motor functions, pain relief, transcutaneous electrical nerve stimulation, defibrillation, surface cardiac pacing, and advanced drug delivery systems 27. Common to these applications are occasional reports of pain, tissue damage, erythema, rash, or burns on the skin at the point where electrodes are placed 1,3,11,18,19,24,28,30,31,33.…”
Section: Introductionmentioning
confidence: 99%
“…In a review by Merrill et al ,20 although mainly for implantable stimulation techniques, several possible mechanisms of injury are discussed which are still pertinent for noninvasive electrical stimulation. A common factor contributing to all the above mentioned mechanisms are regions of high current density 13,17,22,26,27. Overmyer et al 24 modeled this phenomenon and found from experimental observations that the area of the highest temperature increase, or burns, was usually at the edge of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…A few of these applications are defibrillation [15], electroporation [16], bone fracture healing by currents [17], studying electrically induced skin burns [18], specific radiofrequency absorption rate (SAR) distribution measurements [19] and studying brain conductivity changes during transcranial stimulation [20] or spreading depression [21]. Additionally, CDI has become a complimentary method in the verification and development of new electrical impedance tomography (EIT) methods [22,23].…”
Section: Introductionmentioning
confidence: 99%